Pembelajaran Berdiferensiasi Sebagai Strategi Pembelajaran dalam Keragaman Siswa dan Pemenuhan Target Kurikulum di Sekolah Menengah - Lulu Husni Saih (PT PUSTAKA CENDEKIA GROUP, 2024)
This study discusses the role of differentiated learning in meeting curriculum targets in diverse classes, both in terms of ability, learning style, and student background. This study focuses on how differentiated strategies are able to bridge the needs of diverse students while achieving the expected curriculum competencies. Data were collected through qualitative methods, including classroom observations, teacher interviews with class XII IPA students of SMAN 2 Bangkinang Kota. The results of the study indicate that the differentiation approach used in the classroom has not been implemented properly.